Religie a biznes - Gasparski, Wojciech (Annales. Etyka w Życiu Gospodarczym, 2008)
Paper is devoted to the ethical issues of business as considered from the points of view of mainreligions: Christianity – Catholicism and Protestantism – as well as Judaism and Islam. Ethos ofHinduism and the Caux Round Table efforts to disseminate its principles in cooperation with the worldof religion are also mentioned. John Paul II’s and Benedict XVI’s addresses to business leaders arerecalled. Suggestion to establish partnership relations between clergymen and business people is pointedout.